PENYULUHAN PENTINGNYA STATUS GIZI ANAK DAN STUNTING DI DESA UTEUNKOT KECAMATAN MUARA DUA KOTA LHOKSEUMAWE - Mauliza Mauliza; Mutammimul Ula; Zahratul Fitri; Tiara Razaqa Sakinah; Muhammad Rahmad Zainal (LPPM Universitas Al Muslim, 2022)
The incidence of stunting affects chronic growth disorders in children due to long-term nutritional deficiencies. Stunting is caused by multi-dimensional factors, not only caused by malnutrition, which is experienced by pregnant women and children under five. As for other indirect factors, they range from socio-economic factors, parental education, parental occupation, exclusive breastfeeding, immunization status, range of health care facilities, to parenting patterns. The problem of stunting is influenced by infectious diseases and lack of nutritional intake. As for other problem indirect factors, namely socio-economic factors, parental education and parental occupation, exclusive breastfeeding, immunization status, range of health care facilities and inadequate parenting patterns. The method of activity carried out in this community service was by counseling using the lecture method with media presentations containing explanations about how to fulfill nutrition for community service participants. The purpose of this service activity was to increase the knowledge and attitudes of mothers, heads of families and residents of Uteunkot Village in implementing the consumption of balanced nutritious food in children from early age. The results of this counseling activity were able to increase the knowledge of mothers and residents of Uteunkot Village. Furthermore, it is hoped that residents can understand the impact of stunting and how to prevent stunting properly.